ANTI-INFLAMMATORY EFFECT OF CELECOXIB, A COX-2 INHIBITOR, DURING FOREIGN BODY REACTION IN TILAPIA - AUGUSTO, I. L.; OLIVEIRA, S. L.; ARACATI, M. F.; RODRIGUES, L. F.; COTA, C. C.; BELO, M. A. A. (Ars Veterinaria, 2024)
Seeking to understand the defense mechanisms of tilapia to assist in the health management of fish farms, associated with the lack of information on the use of COX-2 inhibitors in teleost fish, this study aimed to identify important aspects involved in the pathophysiology of the chronic inflammatory reaction in Nile tilapia, Oreochromis niloticus, by evaluating the anti-inflammatory activity of celecoxib on the kinetics of migration and formation of gigantocytes in the foreign body response. For this purpose, 72 tilapia were used (Oreochromis niloticus), placed in 9 aquariums (n=8), with a capacity of 100 L of water each, consisting of the following treatments: Control - subjected to inflammatory stimulus without treatment with Celecoxib; TC - Conventional treatment with oral administration of 3mg/kg of Celecoxib after inflammatory stimulus; TP - Prolonged treatment with oral administration of 3mg/kg of Celecoxib for one week before and continuously after the inflammatory stimulus. 8 animals were evaluated per treatment in three periods, that is: 2, 4 and 8 days post-implantation (DPI) of the coverslips, with blood samples being collected to perform the differential leukocyte count in blood extensions, as well as collecting the coverslips. for cytological study. In the later phase of the inflammatory process (8DPI), a decrease in the cellular accumulation of macrophages and formation of polykaryotes was observed on the coverslips of tilapia treated with celecoxib, demonstrating the anti-inflammatory effect of this COX-2 inhibitor, associated with a significant decrease in the number of circulating monocytes in animals receiving conventional treatment. Tilapia treated with celecoxib (TC and TP) showed a significant decrease in total leukocyte count in the initial phase of the inflammatory process (2DPI), characterized by neutropenia and lymphopenia. Therefore, both treatment protocols (TC and TP) with 3mg/kg of celecoxib modulated the foreign body-type inflammatory response of tilapia by acting on the kinetics of macrophage accumulation and formation of polykaryotes on glass coverslips implanted in the subcutaneous tissue, demonstrating a correlation to the dynamics of circulating leukocytes. These results help to understand the role of prostanoids during the chronic inflammatory reaction of tilapia.